Study on Organic Matter Enrichment and Reservoir Characteristics of Permian Longtan Formation Shale in Southeast Sichuan - Cao, Qian; Qi, Minghui; Li, Xiawei; Wang, Daifu; Deng, Yuwei; Wu, Chongyu (Frontiers in Earth Science, 2022)
The study of reservoir space development characteristics and the geochemical parameters of the Permian Longtan Formation in the southeast of Sichuan Basin at Well X1 was analyzed by using core observations, optical thin-section observations, Ar-ion polishing, scanning electron microscopy, and nitrogen adsorption tests. Major and trace elements of samples, the V/Cr, U/T, enrichment coefficients EF (Mo) and EF (U), chemical alteration index CIA and Sr/Cu, as well as Mo, P, and other index values of different samples were calculated based on the test of organic geochemical parameters. The depositional environment of the Longtan Formation in the study area was systematically analyzed. The Longtan Formation was in a warm and humid climate during the deposition period. The main body of the sedimentary water was in an oxy-gen-depleted state, and a portion of it was in an oxidized state with high biological productivity. Therefore, it had a small deposition rate. The clay mineral content and organic matter content in the sample played a major role in controlling the development of reservoir space. The content of clay minerals in the sample was high, and it was mainly chlorite and illite/smectite mixed layer. Under the microscope, it was observed that flake illite/smectite mixed layer and chlorite aggregate mostly developed interlayer pores or microfracture, which played a positive role in the specific surface area and pore volume of the sample.